2022
DOI: 10.3389/fevo.2022.778610
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Stability of Nightingale Song Over Time and Space Using Open, Citizen Science and Shared Data

Abstract: Open science approaches enable and facilitate the investigation of many scientific questions in bioacoustics, such as studies on the temporal and spatial evolution of song, as in vocal dialects. In contrast to previous dialect studies, which mostly focused on songbird species with a small repertoire, here we studied the common nightingale (Luscinia megarhynchos), a bird species with a complex and large repertoire. To study dialects on the population level in this species, we used recordings from four datasets:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Our opportunistic approach indeed led to a large collection of geo-referenced nightingale song recordings. We previously showed that the majority of our CS data were valid enough (Jäckel et al 2021 ) and of high value for dialect studies (Jäckel et al 2022 ). The development of the project over three nightingale breeding seasons has not yet been studied.…”
Section: Introductionmentioning
confidence: 70%
“…Our opportunistic approach indeed led to a large collection of geo-referenced nightingale song recordings. We previously showed that the majority of our CS data were valid enough (Jäckel et al 2021 ) and of high value for dialect studies (Jäckel et al 2022 ). The development of the project over three nightingale breeding seasons has not yet been studied.…”
Section: Introductionmentioning
confidence: 70%
“…Obviously, it is necessary for this that the song types, spreading to new areas, would remain unchanged in the original area of their distribution. The song types are known to persist in populations of some species for decades (Harbison et al 1999, Goodale & Podos 2010, O'Loghlen et al 2013, García et al 2015, Jäckel et al 2022. We have described the survival of many of the Chaffinch song types for 38 years (from 1982 to 2020) in the population of the Zvenigorodskaya Station (Ivanitskii et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Among them, the common nightingale ( Luscinia megarhynchos ) has been praised for centuries for its extraordinary singing behavior 16 , 17 , 18 ( Figure S1 A; Video S1 ). These birds have a seasonal repertoire 19 , 20 of 150–200 different songs 21 , 22 of which one acoustically distinct type is called “whistle songs.” These songs contain relatively unmodulated tonal “whistle syllables” ( Figures 1 A, 1B, and S2 A; and Audio S1 ) and are used in long-range counter-singing duels for territorial defense and mate attraction. 23 , 24 , 25 To quantitatively investigate whether nightingales perform real-time identification and reproduction of the pitch of heard whistle syllables, we performed song recordings of pairs of naturally interacting male nightingales during their mating season in Germany and playback experiments both during their mating season in Germany and in nightingales’ wintering quarters in The Gambia.…”
Section: Introductionmentioning
confidence: 99%